Review of the NARSTO draft report : an assessment of tropospheric ozone pollution : a North American perspective (National Academy Press, 2000)
The report reviews NARSTO's recent report on atmospheric science issues associated with management of airborne particulate matter (PM) to achieve air quality standards. NARSTO is a public-private partnership with members from government, utilities, industry, and academe in Canada, Mexico and the United States that coordinates ozone-related atmospheric science research and assessment.